Can household water sharing advance water security? An integrative review of water entitlements and entitlement failures - Melissa Beresford; Ellis Adams; Jessica Budds; Leila M Harris; Wendy Jepson; Tennille Marley; Chloe Nguyen; Amber Pearson; Anaís Delilah Roque; Asher Y Rosinger; Sameer H Shah; Matthew Stellbauer; et al. (Environmental Research Letters)
An increasing number of studies find that water sharing—the non-market transfer of privately held water between households—is a ubiquitous informal practice around the world and a primary way that households respond to water insecurity. Yet, a key question about household water sharing remains: is water sharing a viable path that can help advance household water security? Or should water sharing be understood as a symptom of water in security in wait for more formalized solutions? Here, we address this question by applying Sen’s entitlement framework in an integrative review of empirical scholarship on household water sharing. Our review shows that when interhousehold water sharing is governed by established and well-functioning norms it can serve as a reliable transfer entitlement that bolsters household water security. However, when water sharing occurs outside of established norms (triggered by broader entitlement failures) it is often associated with significant emotional distress that may exacerbate conditions of water in security. These findings suggest that stable, norm-based water sharing arrangements may offer a viable, adaptive solution to households facing water insecurity. Nevertheless, more scholarship is needed to better understand when and how norm-based water transfer entitlements fail, the capacity of water sharing practices to evolve into lasting normative entitlements, and the impact of interhousehold water sharing on intrahousehold water security.